The Relationship Between Parenting Styles And Student Learning Discipline At MDTA Nurul Amal, Sungai Aur District, West Pasaman Regency - Fitria Fricilia, Frisca; Solfema, Solfema (Universitas Negeri Padang, 2024)
The inspiration behind this study stems from the insufficient level of discipline observed in students' learning. The primary objective is to assess the implementation of democratic parenting patterns among the parents of students, evaluate the extent of students' learning discipline, and investigate the correlation between parents' parenting styles and students' learning discipline at MDTA Nurul Amal Muara Tapus, Sungai Aur District, West Pasaman Regency. Employing a quantitative approach with a correlational research design, the study encompasses a population of 47 individuals from classes III and IV enrolled as students at MDTA Nurul Amal. A sample representing 80% of the population is selected using the Stratified Random Sampling technique. Data is collected through the administration of questionnaires, and for analysis, the percentage and product-moment formulas are employed. The findings indicate a low level of democratic parenting among the parents of students, a low level of students' learning discipline, and a significant correlation between parents' democratic parenting style and students' learning discipline of santri at MDTA Nurul Amal Muara Tapus, Sungai Aur District, West Pasaman Regency. The researcher's suggestions in this study to parents are expected to increase the application of democratic parenting patterns to support children in carrying out high learning disciplineKeywords: Parenting style, Democratic, Discipline